The Impact of Agricultural Output on Economic Development in Nigeria (1986-2014) - , Abula Matthew; , D. Ben Mordecai (Archives of Current Research International, 2016)
This paper empirically examined the impact of agricultural output on economic development in Nigeria using annual time series data spanning 1986 to 2014. Economic development proxied by per capita income (PCI) was explained by agricultural output (AOUT) and public agricultural expenditure (PXA). The study employed the Augmented Dickey-Fuller Unit Root test and the Vector Autoregressive model. The result of the multivariate VAR model indicated that most of the lags of the variables are not significant. However, the high level of the R2 and F value in the VAR regression estimates for PCI gave convincing results that collectively all the lagged terms are statistically significant, implying that agriculture plays an important role in Nigeria’s economic development. The variance decomposition analysis revealed that the greater contribution to shocks in economic development apart from feedback shocks was received from shocks to agriculture. The results of the impulse response function in support of the variance decomposition analysis showed that per capita income responded positively to shocks in agricultural output throughout the ten year period, while the response of PCI to shocks in PXA was negative in the first two year period but became positive throughout the last eight periods. We therefore concluded that agriculture is beneficial and plays a significant role in the development process of Nigerian economy. Hence, the government should increase its expenditure on the sector consistently and ensure that Nigerian economy is diversified, in other words, crude oil should not be the mainstay of Nigerian economy. Also, the government of Nigeria should encourage financial institutions to make certain percentage of their total credit facilities available for the agricultural sector in order to enhance food supply, employment generations, poverty reduction, etc.